Intentional weight loss, weight cycling, and endometrial cancer risk: a systematic review and meta-analysis. Issue 9 (26th August 2019) - Zhang, Xiaochen; Rhoades, Jennifer; Caan, Bette J; Cohn, David E; Salani, Ritu; Noria, Sabrena; Suarez, Adrian A; Paskett, Electra D; Felix, Ashley S
Abstract : Purpose: Weight cycling, defined as intentional weight loss followed by unintentional weight regain, may attenuate the benefit of intentional weight loss on endometrial cancer risk. We summarized the literature on intentional weight loss, weight cycling after intentional weight loss, bariatric surgery, and endometrial cancer risk. Methods: A systematic search was conducted using MEDLINE, Embase, and Cochrane Central Register of Controlled Trials databases published between January 2000 and November 2018. We followed Preferred Reporting Items of Systematic Reviews and Meta-analysis (PRISMA) guidelines. We qualitatively summarized studies related to intentional weight loss and weight cycling due to the inconsistent definition, and quantitatively summarized studies when bariatric surgery was the mechanism of intentional weight loss. Results: A total of 127 full-text articles were reviewed, and 13 were included (bariatric surgery n=7, self-reported intentional weight loss n=2, self-reported weight cycling n=4). Qualitative synthesis suggested that, compared with stable weight, self-reported intentional weight loss was associated with lower endometrial cancer risk (RR range 0.61–0.96), whereas self-reported weight cycling was associated with higher endometrial cancer risk (OR range 1.07–2.33). The meta-analysis yielded a 59% lower risk of endometrial cancer following bariatric surgery (OR 0.41, 95% CI 0.22 to 0.74). Conclusions: Our findings support the notion that intentional weight loss and maintenance of a stable, healthy weight can lower endometrial cancer risk. Strategies to improve awareness and maintenance of weight loss among women with obesity are needed to reduce endometrial cancer risk.